Virtual world : creators, residents, and tourists - Mezianaya, Kira N.; Karaneuski, Konstantin M.; Yashin, Konstantin D. (Cambridge Scholars Publishing, 2019)
The book acquaints the reader with the virtual world, which has become a part of the contemporary entertainment industry, an environment for both professional activity and communication. It discusses the role of computer games in people's lives and the results of computer addiction studies. A separate section is devoted to the theme of Scandinavian mythology, the subjects of which are often present in the virtual world, allowing a comparison to be made between images from ancient myths and legends and their reflection in computer games.